(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigated sociocultural barriers, the variety of sporting events offered in intercollegiate competitions, and gender differences in sports engagement rates among public colleges in Punjab and Khyber Pakhtunkhwa, Pakistan. Employing structured surveys, information was gathered from 300 students (150 per province, 75 male and 75 female) in 12 colleges per province. Significant gender differences were found in the results, with Punjab having higher female participation rates (M = 4.1 hours/week; t(148) = -10.89, p < 0.001) than KP (M = 2.3 hours/week). Compared to Punjab (M = 4.0; t(22) = -4.87, p < 0.001), KP colleges provided fewer sports for female students (M = 2.4). Socio-cultural barriers, including family restrictions (M = 4.3) and lack of facilities (M = 4.6), were stronger in KP, with significant negative correlations with female participation (e.g., r = -0.70 for facilities, p < 0.001). The results demonstrated that, in comparison to Punjab’s urban advantages, KP had more disparities because of cultural and infrastructure limitations. Expanding the selection of female sports, enhancing infrastructure, removing cultural barriers, and putting gender-equity policies into place were among the recommendations. By providing a fresh comparative analysis, this study added to the body of literature and helped shape focused interventions for gender parity in collegiate athletics.